Standard Arabic and Algerian Languages: A sociolinguistic Approach and a Grammatical Analysis - Kerras, Nassima; Baya E., Moulay-Lahssan (Íkala, Revista de Lenguaje y Cultura, 2019)
This research study aims to present a comparison between Arabic language grammar and Algerian dialect grammar. Algerian is used daily by Algerians resident in Algeria and other regions. Political discourses are performed in Algerian, as well as advertising, television series, film, radio, communication through social media, and so on. Arabic is Algeria’s official language. Despite its importance over the world, its use is limited to writing, inter-national communication between Arabian nations, and instruction. The importance of Arabic is present in Algeria, but the country’s mother tongue is Algerian —along with Tamazight, which is used in some regions—. This language belongs to over 42 million inhabitants, who use it on a daily basis to convey their needs and feelings; hence the importance to study its evolution, grammar, and use. The purpose of comparing both languages was to understand the inner workings of a living language, little studied by linguists.